Entlasten! Aber wie? Wege im Dschungel der Möglichkeiten; Navigating the jungle of possibilities - Nadine Riedel; Andreas Peichl (Wirtschaftsdienst, 2022)
– Living costs in Germany have surged since Russia's attack on Ukraine. In this article, we discuss pros and cons of different government policies to protect affected citizens. There is a vast domain of possible relief options, each coming with its own trade-offs and design pitfalls. Information gaps in German public administration render desirable options like income and energy-use-contingent transfers administratively infeasible. These frictions should be addressed - if not for the present, then for the next crisis. With regard to other options, governments must be mindful to design policies that are well-targeted to people in need and that do not distort incentives to reduce energy consumption. Possibilities for that do exist.
Keywords: H12; H53; 330; Wirtschaftskrise; Energiepreis; Finanzpolitik; Deutschland